IMMUNOHISTOCHEMICAL PARAMETERS OF TGAB AND FOX–1 EXPRESSION IN THE THYROID GLAND OF RATS AFTER PRENATAL ANTIGEN EXPOSURE - Fedosieieva О.V.; Chaikovsky, Yu.B. (World of Medicine and Biology, 2021)
The results were obtained about features of thyroglobulin and Fox–1 expression in rat’s thyroid, as immunomorphological markers of thyroid morphogenesis, the formation of the synthetic apparatus and its functional activity, after prenatal antigenic action by staphylococcal toxoid. In the process of morphogenesis and establishment of the synthetic function of the thyroid gland after the prenatal action of staphylococcal toxoid, two aberrant intersections in nuclear and cytoplasmic Fox–1 expression were detected among themselves and with indicators of proliferative activity. In the thyroid gland, such aberrant intersections occur from the 3–7 days and the 14–21 days, which indicates the intensification of the processes of establishment and normalization of structural and functional units of the thyroid gland. These data correlate with the expression of thyroglobulin, both cytoplasmic and colloidal, which is respectively expressed by signs of secretory inversion of thyroglobulin first with morphological signs of hypofunction up to 14 days, which then change to hyperfunctional.